-3.1(7.5w+7)-6=

Simple and best practice solution for -3.1(7.5w+7)-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.1(7.5w+7)-6= equation:


Simplifying
-3.1(7.5w + 7) + -6 = 0

Reorder the terms:
-3.1(7 + 7.5w) + -6 = 0
(7 * -3.1 + 7.5w * -3.1) + -6 = 0
(-21.7 + -23.25w) + -6 = 0

Reorder the terms:
-21.7 + -6 + -23.25w = 0

Combine like terms: -21.7 + -6 = -27.7
-27.7 + -23.25w = 0

Solving
-27.7 + -23.25w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '27.7' to each side of the equation.
-27.7 + 27.7 + -23.25w = 0 + 27.7

Combine like terms: -27.7 + 27.7 = 0.0
0.0 + -23.25w = 0 + 27.7
-23.25w = 0 + 27.7

Combine like terms: 0 + 27.7 = 27.7
-23.25w = 27.7

Divide each side by '-23.25'.
w = -1.191397849

Simplifying
w = -1.191397849

See similar equations:

| 293+6y= | | 19x-(6x-9)=87 | | 20+5h=25 | | DX+HY= | | 293+6y=500 | | 0.75x+1.5=6x+72 | | 2ln(x-5)=54 | | 7.5(-3.1w-6)+7= | | 7(x+10)=210 | | -6/5y=42 | | 7a=12 | | 10x+4=p | | 25x^2-10=2 | | ax-b=cx-7 | | 2b^2-9b+9= | | 7(x+5)=6(x-6)+x | | 3x-5=-6x+14 | | 3x-5=-6+14 | | 6y+9+9y= | | 9f+9f=2 | | 4.5(7.6z+3)-3= | | lnx+x=5 | | 5x^2+6x+13=0 | | 9y-11=-10x+5 | | 7.6(4.5z-3)+3= | | y+8=7x | | ln(m)=.5(ln(x^2-y)) | | x/2-29=22 | | -5(-3)(-7)(-1)= | | 7(x+3)+2=7x+9 | | 3x^2/3x | | 0.18(2x)=29.5 |

Equations solver categories